Ritual Balimau Menyambut Ramadhan: Makna Dan Relevansinya Bagi Masyarakat Minangkabau - Vadisa, Vadisa Vadisa; Amalia Putri, Riza Qori; Istiyanto, S Bekti (AGUNA: Jurnal Ilmu Komunikasi, 2024)
Indonesia is a country that has many islands, namely from Sabang to Merauke. This is not spared from the diversity of cultures, religions and customs from each region, one related to beliefs. One of them is Islam, according to believers of Islam, growing and developing around the world wrapped in different customs and customs. In welcoming the month of Ramadan, each region must have its own way to welcome the month of Ramadan, one of which is the Minangkabau people. The Minangkabau people in West Sumatra province have various rich cultural traditions in welcoming the holy month of Ramadan. Balimau is a tradition of bathing using lime juice that develops among the Minangkabau people and becomes a ritual or tradition when welcoming the holy month of Ramadan, the Balimau Bathing Ritual is considered a bath for self-purification for the Minangkabau people. The purpose of this research is to find out the meaning and relevance of Balimau rituals in welcoming Ramadan for the Minangkabau people. The research method used by the researcher in this study is a literature study research method. So that the data needed in this study comes from Literature Sources, journals and other documents. The results of the study show that the Balimau ritual has a deep spiritual meaning and its social relevance for the Minangkabau people and it is suggested that efforts to preserve the Balimau ritual continue to be improved so that this ritual does not lag behind the existing modernization so that it can continue to be improved through various modern approaches. Thus, this Balimau activity can have a ritual sustainability so that it is maintained in the current flow of globalization and modernization. Keywords: Indonesia; Ramadhan; Islam; Minangkabau; Ritual